Beetles (coleoptera) - Cabral-de-Mello, Diogo C. [UNESP] (Taylor & Francis, 2014)
The Coleoptera order (beetles) comprises the most species-rich group among the insect class, corresponding to approximately 40% of this class and 30% of all animals, encompassing more than 350,000 described species distributed worldwide (Lawrence 1982; Lawrence and Britton 1994; Arnett and Thomas 2001; Arnett et al. 2002). Although a large number of species have been cataloged, the number of beetle species described so far could be less than the real diversity of the group, and according to Terry Erwin (1982), the total number of beetles on the planet could be estimated at 12,000,000. In contrast, more recent revisions proposed the occurrence of 850,000-4,000,000 living species (Hammond 1995; Stork 1999; Nielsen and Mound 1999).